A multidisciplinary pulmonary embolism response team (PERT)—experience from a national multicenter consortium. (1st August 2019) - Schultz, Jacob; Giordano, Nicholas; Zheng, Hui; Parry, Blair A.; Barnes, Geoffrey D.; Heresi, Gustavo A.; Jaber, Wissam; Wood, Todd; Todoran, Thomas; Courtney, D. Mark; Naydenov, Soophia; Khandhar, Sameer; et al.
Abstract : Background: We provide the first multicenter analysis of patients cared for by eight Pulmonary Embolism Response Teams (PERTs) in the United States (US); describing the frequency of team activation, patient characteristics, pulmonary embolism (PE) severity, treatments delivered, and outcomes. Methods: We enrolled patients from the National PERT Consortium™ multicenter registry with a PERT activation between 18 October 2016 and 17 October 2017. Data are presented combined and by PERT institution. Differences between institutions were analyzed using chi‐squared test or Fisher's exact test for categorical variables, and ANOVA or Kruskal‐Wallis test for continuous variables, with a two‐sided P value < 0.05 considered statistically significant. Results: There were 475 unique PERT activations across the Consortium, with acute PE confirmed in 416 (88%). The number of activations at each institution ranged from 3 to 13 activations/month/1000 beds with the majority originating from the emergency department (281/475; 59.3%). The largest percentage of patients were at intermediate–low (141/416, 34%) and intermediate–high (146/416, 35%) risk of early mortality, while fewer were at high‐risk (51/416, 12%) and low‐risk (78/416, 19%). The distribution of risk groups varied significantly between institutions ( P  = 0.002). Anticoagulation alone was the most common therapy, delivered to 289/416 (70%) patients with confirmed PE. The proportion of patients receiving any advanced therapy varied between institutions ( P  = 0.0003), ranging from 16% to 46%. The 30‐day mortality was 16% (53/338), ranging from 9% to 44%. Conclusions: The frequency of team activation, PE severity, treatments delivered, and 30‐day mortality varies between US PERTs. Further research should investigate the sources of this variability.